Manure and adoption of modern seeds in cereal‐based systems in West African drylands: linkages and (non)complementarities - (:unkn) unknown (My University, 2018)
Using a stepwise approach that combines several econometric methods, we assessed whether or not the adoption of modern seeds and the use of manure in cereal‐based systems are linked and, if so, what are the driving forces of the linkages between these two agricultural technologies under dry‐climate conditions in West Africa. We found complementary and substitutability linkages arising from jointness and endogeneity between the two technologies. Specifically, our findings reveal positive joint determination along with negative endogeneity between the two technologies indicating that, controlling for observable variables, both technologies are positively linked, but unobserved factors that affect one adoption decision are negatively correlated with the other. After controlling for jointness and endogeneity, we found significant complementarity linkages showing a significant positive effect of manure use on the adoption of modern seeds, which is also significantly and positively affected by the number of cash crops grown and remittances. The two technologies are reversely affected by schooling and the incidence of soil fertility problems within the farm, whereas the amount of healthy land has a positive effect on both. The study suggests that organic fertilizer can serve as an enabling factor for greater adoption of modern seeds, especially in less favourable climate areas, and strongly supports the argument behind the need to breed seeds suitable for the use of organic fertilizers. These findings provide avenues for re‐orientation of policies that promote the use of modern seeds in dryland areas in sub‐Saharan Africa, with a possibility of breeding and promoting them in packages with organic fertilizers to upscale their adoption.
Keywords: African Research